Media Belajar dan Gaya Belajar Dengan Hasil Belajar Evaluasi Pembelajaran PAI di STIT Palapa Nusantara - Fahri, Lalu Moh. (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Palapa Nusantara Lombok NTB, 2014)
This research aims to understand about the relationship between media and learning learning style with a student learning outcomes the course learning evaluation PAI in high school Science Tarbiyah (Å TÃT) Palapa Lombok Indonesia by using research methods korelasional. Results of the research there is a relationship between media and learning and learning styles with the results of the study. Which is the more complete study or media support in the learning process and learning outcomes of students getting better and getting good student learning style then the better learning results anyway.